Criminal compliance in the peruvian criminal law - Clavijo Jave, Camilo (2014)
First, this work proposes a study of the origin, elements and application of the Compliance Program or, also named, Regulatory Compliance Program. The aforementioned program is understood as an internal device that corporations use not only to comply with the current legislation but also to prevent and detect legal violations they could be found in or as part of the activities they carry out.Second, it tries to explain and develop the connection between, on one hand, the new risks in the financial and technological development and, on the other hand, Criminal Law as a protective body of important legal assets for society. The aim is to analyze Criminal Compliance to get the corporationto manage its activities under current legislation, especially Criminal Law.In this regard, it enlarges the sectoral developments based on the Peruvian Government’s implementation of the the Compliance Program in the legal framework.Finally, it analyzes the impact of Criminal Compliance in the criminal legal framework. For that end, it refers to the criminal liability system in Peru and in what way it impacts on the application of Criminal Compliance.